Comparação entre as diferentes regulamentações existentes relacionadas a auditoria contábil no mercado de capitais na abertura de capital, emissão de títulos, empréstimos e fusões e aquisições - Silva, Adilson Afonso da (2013)
The auditor has is important for the capital market because it´s increasing the quantity of companies that are looking for such market as an alternative and way to raise funds to invest in their operations. This market offers many options for raising funds and in most of these operations the company is required to have its financial statements audited. Depending on the operation performed by the company or the transaction chosen by the company, such company needs to follow the specific regulation issued by a regulatory agency responsible for such sector or market. This agency is responsible for both, for issuing regulations related to the industry and for rmonitoring the companies operations in a supervision way. In addition to requiring the audited financial statements, the regulators often require additional work of auditors in order to get additional credibility of the information provided by these companies. Some procedures required by the regulators are common or similar and others are specific. This difference in requirements makes the auditor seeks a constant update and an extensive knowledge of the markets where it operates. This growing capital market has required auditors' greater involvement and participation by giving more credibility to financial and accounting data disclosed by companies. The objective of this dissertation is to demonstrate the main requirements issued by the regulators, specifically BACEN and CVM, related to the auditor and specifically related to auditing the financial statements. The purpose is also to focus on capital markets. We have conducted a search of the major normatives issued by such regulators of the market and compared them to identify convergences and divergences. The focus of this research was to comparatively describe the work performed by the auditor on accounting audit based on the capital market. The main operations were considered: i) initial public offering of shares (open capital) or (Initial Public Offering - IPO), ii) the issuance of bonds in the local market and abroad (bonds, debentures and other) and obtaining loans and iii) the process of mergers and acquisitions and privatizations (where the auditor's process support and support analyzing accounting information before completing the acquisition transactions "due diligence"). As a result we found that specifically in accounting audit there is no relevant differences in the regulatory requirements of the Central Bank and the CVM, regulators considered for such research. Both even issuing their own rules, make reference to the same audit requirements defined by the CFC and Ibracon. We found that each agency defines different periodicities for auditing and specific accounting standards, as the case of the Central Bank, but all have the same goal and the requirements are very close. Related to operations of the capital markets that are not regulated as mergers and acquisitions, we fond that the work is set by client or contractor and the scope may vary and even the format of each report case by case